Life-stage factors associated with overweight severity in adolescents - Dut, Raziye; Videira-Silva, Antonio; Vilardouro, Ana Sofia; Freira, Silvia; Fonseca, Helena (The Turkish Journal of Pediatrics, 2020)
Background. Investigating life-stage factors associated with overweight may be useful in the prevention of excessive BMI increase. The main aim of this study was to investigate the influence of the route of delivery, birth weight and overweight onset on overweight severity in a sample of overweight adolescents followed at a Pediatric Obesity Clinic. Methods. Clinical data from 412 adolescents with overweight (BMI ≥ p85), aged 10-18 were retrospectively collected and analyzed. Results. Adolescents born by cesarean section (CS) showed a lower age of overweight onset, compared to other methods of delivery (d= 0.33, p= .009). Birth weight was positively associated with BMI z-score (r=.164, p= 002) and waist circumference (WC) (r=.191, p=.001). The overweight onset was negatively associated with BMI z-score (r= -.277, p < .001), WC (r= -.270, p < .001) and body fat mass (r= -.199, p=.001). Overweight duration was the best predictor of BMI z-score, explaining in 75% its variation (F=1,317)=26.94, p < .001), which increased to 99% when birth weight was included in the model (F(2,316)=18.47, p < .001). Conclusions. This study suggests that lifestyle may interrupt the burden of CS on BMI z-score throughout growth. Moreover, increased birth weight may anticipate overweight onset, and consequently overweight duration in the presence of inadequate lifestyle behaviors.
Keywords: adolescent; birth weight; overweight; overweight severity; way of delivery